SEMINAR ON AUTO-PROFIT FROM SOCIAL MEDIA (NO NEED TO BE A CELEBRITY AS LONG AS YOU KNOW THE TRICKS) - Muhammad Fikry Januar Januar; Sekar Fauziah Larasati; Solihin; Imma Ismaniar; Dede Ibrahim Maulana; Mochamad Anjar Albagja; Endra Abdul Hadi; Nurdiansyah Permana (Politeknik Mardira Indonesia, 2025)
The development of social media offers new economic opportunities, but public understanding of strategies for utilizing it to generate income remains low. Lack of digital literacy, digital marketing skills, and content creation skills are major obstacles to optimizing social media as an economic tool. The seminar